Deeds or words? The local influence of anti-immigrant parties on foreigners' flows in Italy - Augusto Cerqua; Federico Zampollo (Global Labor Organization (GLO), 2021)
We investigate the influence of anti-immigrant parties on foreigners' location choices in Italy. Considering municipal elections from 2000 to 2018, we create a database that includes a scientific-based classification on the anti-/pro-immigration axis of all Italian political parties based on experts' opinions. Via the adoption of a regression discontinuity design, we find that the election of a mayor supported by an anti-immigrant coalition significantly affect immigrants' location choices only when considering the most recent years. This finding does not appear to be driven by the enactment of policies against immigrants but by an 'inhospitality effect', which got stronger over time due to the exacerbation of political propaganda at the national and local level.
Keywords: D72; J61; C13; 330; immigration; political parties; regression discontinuity design